Змагальність, диспозитивність, рівність сторін - принципи кримінального процесу України - Грицаєнко, Л.Р. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article deals with to the constitutional principles of the legal proceeding and problem of their realization in criminal procedure of Ukraine.